The Interweaving between Verbal and Visual Text in the Works of the Brothers van Eyck and Rogier van der Weyden: Identifying the Viewer’s Position - Zabrodina, Elena A. (Actual Problems of Theory and History of Art, 2017)
Although the use of labels in visual arts has millennia of practice, it was the brothers Van Eyck and Rogier van der Weyden who managed to intertwine verbal and visual aids in their work in such a unique way as are the sources of written texts that include prophecies, apocrypha, “Golden legend”, “Imitation of Christ”, the words of the Saviour, the apostles and the church fathers, personal mottos, and the works of ancient authors.The inscriptions and signatures in the works of the two masters of the Northern Renaissance are among the least studied problems. Many features of the inscriptions on the works by Van Eyck and Van der Weyden are close to each other and reveal different aspects of the viewer’s position, which is expected by the artists. The dialogues of Gospel characters manage emotions and direct the audience’s attention by means of a written text, scrolls with texts in the hands of the Sibyls and Angels create the effect of trompe-l’oeil, inverted writing responsesreminiscent of the “internal viewer” works. It should be noted that Van Eyck uses three languages — Greek, Latin, Flemish, as well as the letters of the Jewish alphabet, whereas in van der Weyden’s works only Latin letters have been found. And the most interesting fact is that Jan van Eyck often makes a viewer look into a picture tosee the text as part of embroidery on a dress or an inscription on a stone pedestal. On the other hand, Rogier van der Weyden often puts a text on floating ribbons (“banderole”), thereby creating an “interpretive gap”, which allows a viewer to reflect on the relationship between the visual and the verbal.
Keywords: inscriptions; Ghent Altarpiece; the van Eyck brothers; Jan van Eyck; Rogier van der Weyden; Nicholas of Cusa; Madonna of Chancellor Rolin; Saint Columba altarpiece; Duran Madonna; Claus de Werve; Leal Souvenir; Braque Triptych; early Netherlandish painting; Northern Renaissance